Kondisi Pola Hujan Terhadap Pembangunan Matos Di Kota Malang - Apriliyanti , Ayu; Khaerudin , Dian Noorvy ; Rahma , Pamela Dinar (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
Changing open land to closed land will increase air temperatures in urban areas. Like the development of Malang Town Square which was built in 2005 which is not in accordance with the Regional Spatial Planning (RTRW) of Malang. The purpose of the study was to analyze the rainfall patterns from the impact of Malang Town Square development. The method used is to find monthly maximum daily rainfall data which is then analyzed and graphed to determine monsoonal rainfall patterns. From the two graphs it can be concluded that the graphs in the years before the construction of the highest rainfall pattern matos were in January but in the years after the construction of the highest rainfall pattern matos were in December. So that changes in land use have an impact on rainfall patterns in an area. This study only analyzes the impact of the construction of matos on rain patterns three years before development and three years after the construction of Malang Town Square